Building versatile audio crossfades using recurrence relations - Lupsa-Tataru, Lucian (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
The audio crossfade is a well-known technique used to perform smooth transitions between two audio contents (segments) by fading out one content and, simultaneously, fading in the other. This effect is commonly used in music production, film and TV sound design, podcasting, creation of simulation software, media development and entertainment software, respectively. In order to help with blending different styles, tempos, and even genres smoothly, and to create a more natural and seamless flow in audio, we propose a procedure of building highly versatile audio crossfade effects, adaptable across different scenarios. To facilitate the implementation of real-time crossfades, each fade envelope is generated by employing a recurrence relation that yields the current value of the audio volume as rational function of its previous value.